If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 108 = 8y Reorder the terms: 108 + 2y = 8y Solving 108 + 2y = 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 108 + 2y + -8y = 8y + -8y Combine like terms: 2y + -8y = -6y 108 + -6y = 8y + -8y Combine like terms: 8y + -8y = 0 108 + -6y = 0 Add '-108' to each side of the equation. 108 + -108 + -6y = 0 + -108 Combine like terms: 108 + -108 = 0 0 + -6y = 0 + -108 -6y = 0 + -108 Combine like terms: 0 + -108 = -108 -6y = -108 Divide each side by '-6'. y = 18 Simplifying y = 18
| 28u-10u=175 | | x/7=4/21 | | -5x=-45000 | | -2a+2-5a=-14 | | 4+6=7x-5 | | 125-13x=21x-75 | | f(n)=n | | f(n)=n+3 | | -7(3a-4)+1=-10a-59 | | 4y+7y-9=180 | | 30x^2-3x-6=0 | | 15x-30=720 | | 1=(2)/(x^2)-(x-1)/(x+1) | | 12.5+0.5m=42 | | 4y+6y=y | | 24x^2+48=0 | | 23-x/4=11 | | V=0.125s | | (1-6i)-(5+4i)-(-6+i)= | | 9n+6+9=0 | | .4h-7=2.4-2h+3 | | 2x^2+x+j=0 | | 3x^2-36x+12=0 | | r+.25=.75 | | -(2f-4)=-4(-f+2) | | 3y-1+y+29=6y+30-4y | | -t+5=5-19 | | -3=-6/5*2+b | | ((5x^2)-2x)*((x^2)-x+5)=0 | | 16a^2-81y^2=0 | | -3z+15=6z-13 | | -3(5m-10)=67 |